Characteristics of CTEV Patients at Orthopedic and Traumatology Outpatient Clinic in Datu Beru General Hospital Takengon Central Aceh Period August 2018-July 2022 - Ongko Setunggal Wibowo; Subhan Thaib (Journal Orthopaedi and Traumatology Surabaya, 2022)
Background: Congenital Talipes Equinovarus (CTEV) is a congenital disorder commonly occurring in newborns. The word talipes equinovarus comes from Latin: tali mean ankle, pes means foot, equino means plantar flexion, and varus means midline deviation. CTEV cases occur 1-2: 1000 live births, cases in males are more frequent than in females and can occur unilateral or bilateral. Bilateral conditions occur in half of the total number of cases. The aim of this study is that, in the future, especially parents know about this disorder so there will be no misinformation. Methods: This study uses a descriptive research method with a cross-sectional design that aims to determine the characteristics of CTEV patients at the Orthopedic and Traumatology Outpatient Clinic in Datu Beru General Hospital Takengon Central Aceh for August 2018-July 2022. Sampling was carried out by non-probability sampling and using the purposive sampling technique. This is a non-random sampling technique with specific considerations from the researcher (inclusion and exclusion criteria). Results: The number of births in Central Aceh Regency from August 2018-July 2022 amounted to 15,206. The incidence of CTEV in that period was 22 cases with a ratio of 1.4: 1000 live births. Conclusion: Males 15 cases (53.6%) and females 13 cases (46.4%). The age of patient's brought by parents was mostly1-6 months, with as many as 12 cases (42.9%). Bilateral conditions were 13 cases (46.4%), and 15 (53.6%) were unilateral. On average, patients with CTEV were corrected 5.2 times using the Ponseti method.